Homo and heterotypic stressor induced immunomodulatory changes in the lymphoid organs of the rats at different stages of early postnatal development / Azhar Ahmad - Ahmad, Azhar (2017)
Stress is a part of modern life. It causes serious alterations in the nervous, endocrine, immune, cardiovascular, reproductive and digestive systems. Different types of stress with different types of stressors induce diverse changes in the body. Heterotypic stress with variable stressors triggers an activation pattern in the neuroendocrine system which is different from the homotypic stressor with comparable characteristics (intensity, duration, etc). Immune system is the one most sensitive to stress. Research on the effect of heterotypic stress on the immune system is scarce. Data regarding effect of heterotypic stress on the immune system during prepubertal period of postnatal development are few, mainly involving weight of the lymphoid organs. These data might help to develop addressed measures of prophylaxis of post-stress immunosuppression in children. The objectives of this research are to evaluate immunomodulatory effect of heterotypic vs. homotypic stress on the morphology of the lymphoid organs in the prepubertal experimental animals of different age groups. Sprague Dawley rats aged 15, 30 and 60 days were chronically exposed to homo- or heterotypic stress. Thymus, spleen and lymph nodes were evaluated using immunohistochemically morphometry of cells expressing markers of immunocytes, stromal cells, proliferation and apoptosis respectively. Chronic heterotypic stress exposure showed more significant immunosuppressive effect in the central and peripheral immune organs compared to the homotypic stress, as demonstrated by image analysis of histological slides stained for markers of T-lymphocytes; Lymphocytes, apoptosis and proliferation. The dominating mechanism of cell depletion in the preweaning and infant animals was reduced recirculation rate of Tlymphocytes in the thymus while in the juvenile rats was increased apoptotic rate of lymphoid cells and decreased immigration rate of T-lymphocytes from the thymus to the peripheral immune organs. Heterotypic stress also affected interplay of stromal and lymphoid cells in the age-related manner. Thus, in chronic heterotypic stress central and peripheral lymphoid organs exhibited complex age-dependent immunomodulatory changes associated with a crosstalk of the developmental and post-stress changes in the neuroimmunoendocrine axis of the growing body.